Mathematics Literacy Ability in Terms Of Self Efficacy in Cooperative Learning Type of Group Investigation Model With Humanism Approach Assisted by Schoology - Annisa Indrawati, Fiqi; Wardono, Wardono; Junaedi, Iwan (Universitas Negeri Semarang, 2021)
The purpose of this study is to describe the ability of students' mathematical literacy in terms of self efficacy in group investigation learning with humanism approach assisted by schoology. This research is a type of qualitative research. The research approach used is a descriptive approach. Data collection is done by self efficacy assessment scale, interview guidelines and observation. The subject of the research was class X MIPA 6 of SMAN 1 Juwana. The results showed that the qualitative data analysis at the planning and preparation stages, syllabus, lesson plans, teaching materials, worksheets, mathematics literacy ability tests, interview guide sheets and student response sheets were categorized as very good. At the classroom enviroment stage, the implementation of learning that has been delivered in the category of very good quality and at the professional responsibility stage, more than 75% of the majority of students assess that learning has been carried out properly. Based on the analysis of the interview data, it was found that each type of self efficacy has different mathematical literacy abilities. This is indicated from 5 students in the category of self efficacy magnitude, there are 2 categories of high and 3 categories of medium, from 6 students category of strenght there are 1 category of medium and 5 categories of low, from 22 students the category of generality there are 7 categories of high, 12 categories of medium and 3 categories of low